Risk Governance, Regulatory Enforcement, and Profitability in Nigerian Banks: Evidence from a Decade of Financial Reforms - Oyasor, Emmanuel Imuede (International Journal of Economics and Financial Issues, 2025)
This study examines how credit risk management influences the profitability of banks in Nigeria, focusing on key variables such as capital adequacy, non-performing loans (NPLs), liquidity, and loan-to-asset ratios. Employing multiple regression and panel data analysis, the research evaluates data from 15 Nigerian banks over the 2013–2023 period. The results reveal that strong credit risk practices, including diligent loan monitoring and proactive NPL handling, positively impact profitability. Nevertheless, issues like high offshore borrowing and weak risk framework implementation undermine financial stability. The study concludes that while regulatory policies are beneficial, their inconsistent enforcement and institutional shortcomings pose significant barriers. Accordingly, it recommends improving risk management systems, enforcing regulations more consistently, diversifying loan portfolios, and minimizing dependence on offshore funding to boost profitability and enhance financial stability in Nigerian banks.